Making grades matter : standards-based grading in a secondary PLC at work - Townsley, Matt; Wear, Nathan L. (Solution Tree Press, 2020)
"In Making Grades Matter: Standards-Based Grading in a Secondary PLC authors Matt Townsley and Nathan L. Wear provide readers with a practical guide toward the implementation of the standards-based grading system. Although much has been written about the concept and advantages of standards-based grading, in this book, the authors focus specifically on implementing the framework at the secondary level with the vital support of a professional learning community (PLC). As such, this book provides a roadmap that secondary school educators and administrators working in a PLC can utilize to initiate the multiyear process toward implementing standards-based grading schoolwide or districtwide. Not only are each of the practices needed for this change covered in detail, but each practice is connected directly with one of three foundational principles of standards-based grading. In this book, readers will find all of the tools, resources, and guidance they need to not only implement the standards-based grading system in their schools but, through collaborative work within a PLC, achieve the greatest possible success with it"--